Genetic characterization and molecular cloning of the tripeptide permease (tpp) genes of Salmonella typhimurium. - Gibson, M M (1984)
Of the three bacterial peptide transport systems only one, the oligopeptide permease, has been characterized in any detail. We have now isolated Salmonella typhimurium mutants deficient in a second transport system, the tripeptide permease (Tpp), using the toxic peptide alafosfalin. Alafosfalin resistance mutations map at three loci, the gene encoding peptidase A (pepA) and two transport-defective loci, tppA and tppB. Locus tppA has been mapped to 74 min on the S. typhimurium chromosome, cotransducible with aroB, and is a positive regulator of tppB. Locus tppB maps at 27 min in the cotransduction gap between purB and pyrF. We cloned tppB, the structural locus for the tripeptide permease. Two simple methods are described for mapping the location of cloned DNA fragments on the chromosome of S. typhimurium.